2015
DOI: 10.1152/jn.00070.2015
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory spatial attention modulates amplitudes, latencies, and latency jitter of laser-evoked brain potentials

Abstract: Several studies provided evidence that the amplitudes of laser-evoked potentials (LEPs) are modulated by attention. However, previous reports were based on across-trial averaging of LEP responses at the expense of losing information about intertrial variability related to attentional modulation. The aim of this study was to investigate the effects of somatosensory spatial attention on single-trial parameters (i.e., amplitudes, latencies, and latency jitter) of LEP components (N2 and P2). Twelve subjects partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 49 publications
3
29
0
Order By: Relevance
“…This set is then applied to single trials and allows latency and amplitude to be determined for each ERP peak. This analysis has been suggested to offer a more accurate and unbiased estimation of ERPs latency and amplitude (Hu et al 2011).In their results, Franz et al (2015) observed that, irrespective of the method that was used (standard averaging or single-trial analysis), N2 peaks were larger in the attended condition. This would suggest that the effects of spatial attention on the magnitude of the N2 peak are not influenced by possible latency jitters occurring at the single-trial level.…”
mentioning
confidence: 93%
See 4 more Smart Citations
“…This set is then applied to single trials and allows latency and amplitude to be determined for each ERP peak. This analysis has been suggested to offer a more accurate and unbiased estimation of ERPs latency and amplitude (Hu et al 2011).In their results, Franz et al (2015) observed that, irrespective of the method that was used (standard averaging or single-trial analysis), N2 peaks were larger in the attended condition. This would suggest that the effects of spatial attention on the magnitude of the N2 peak are not influenced by possible latency jitters occurring at the single-trial level.…”
mentioning
confidence: 93%
“…Several studies have shown that attention is able to modulate behavioral and brain responses to noxious inputs (see Legrain et al 2012 for a review on event-related potentials, ERPs). However, attention is not a unitary construct; indeed, different attentional processes have been identified, and a systematic investigation of the physiological mechanisms through which these different processes can shape nociception remains elusive.In their recent article, Franz et al (2015) provide an interesting perspective on the mechanisms through which spatial attention (i.e., attention allocated to a specific spatial location) exerts its modulation on brain responses to nociceptive laser stimuli (i.e., laser-evoked potentials, LEPs). The authors aimed to investigate not only the effects of attention on the magnitude of the response but also the effects on the latency of the response, with a particular focus on the trial-to-trial variability.…”
mentioning
confidence: 99%
See 3 more Smart Citations